Analisis Pengaruh Ceo Turnover, Opini Audit dan Pertumbuhan Perusahaan terhadap Auditor Switching dengan Financial Distress sebagai Variabel Moderasi - Indah Kristianti; Vinola Herawaty (Penerbit Goodwood, 2023)
Purpose: This study aims to examine and analyze the effect of CEO Turnover, Audit Opinion, Company Growth on auditor switching with financial distress as a Moderating Variable. Methodology/approach: The type of data used in this study is secondary data, in the form of financial reports and annual reports. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Sample data were obtained by purposive sampling method with the features of voluntary auditor changes or under 6 years. So that the final number of samples obtained was 140 data. The data analysis technique used is logistic regression analysis. Results/findings: The research results show (1) CEO Turnover has a positive effect on auditor switching (2) Audit opinion has no effect on auditor switching (3) Company growth has no effect on auditor switching (4) Financial Distress has a positive effect on auditor switching (5) Financial Distress strengthens the influence CEO turnover on auditor switching (6) financial distress is not able to influence the effect of audit opinion on auditor switching (7) financial distress is not able to moderate the effect of company growth on auditor switching.